1992
DOI: 10.1042/bj2810359
|View full text |Cite
|
Sign up to set email alerts
|

Relative expression of cytochrome P450 isoenzymes in human liver and association with the metabolism of drugs and xenobiotics

Abstract: Cytochrome P450s play a central role in the metabolism and disposition of an extremely wide range of drugs and chemical carcinogens. Individual differences in the expression of these enzymes may be an important determinant in susceptibility to adverse drug reactions, chemical toxins and mutagens. In this paper, we have measured the relative levels of expression of cytochrome P450 isoenzymes from eight gene families or subfamilies in a panel of twelve human liver samples in order to determine the individuality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(111 citation statements)
references
References 63 publications
7
104
0
Order By: Relevance
“…However, a number of studies utilising various experimental models of Ang II-dependent hypertension, including two-kidney, one-clip (2K1C) Goldblatt hypertensive rats, Ang II-infused hypertensive rats, and TGR(mRen2)27 transgenic rats, have clearly demonstrated that intrarenal levels of Ang II can be dissociated from both circulating Ang II concentrations and kidney renin content. [10][11][12][13][14][15][16] Indeed, Ang II contents in the non-clipped kidney of 2K1C Goldblatt hypertensive rats and in kidneys from Ang II-infused rats and hypertensive TGR(mRen2)27 transgenic rats are higher than can be explained on the basis of circulating Ang II levels even though these kidneys are markedly renin-depleted. [10][11][12][13][14][15][16] In the Ang II-infused hypertensive rat, chronic administration of an AT 1 -receptor antagonist prevents the hypertension and the associated increase in intrarenal Ang II levels, 13,17,18 suggesting that in this hypertensive model the augmentation if intrarenal Ang II levels is mediated in part by AT 1 -receptor-mediated uptake of Ang II.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C Tmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a number of studies utilising various experimental models of Ang II-dependent hypertension, including two-kidney, one-clip (2K1C) Goldblatt hypertensive rats, Ang II-infused hypertensive rats, and TGR(mRen2)27 transgenic rats, have clearly demonstrated that intrarenal levels of Ang II can be dissociated from both circulating Ang II concentrations and kidney renin content. [10][11][12][13][14][15][16] Indeed, Ang II contents in the non-clipped kidney of 2K1C Goldblatt hypertensive rats and in kidneys from Ang II-infused rats and hypertensive TGR(mRen2)27 transgenic rats are higher than can be explained on the basis of circulating Ang II levels even though these kidneys are markedly renin-depleted. [10][11][12][13][14][15][16] In the Ang II-infused hypertensive rat, chronic administration of an AT 1 -receptor antagonist prevents the hypertension and the associated increase in intrarenal Ang II levels, 13,17,18 suggesting that in this hypertensive model the augmentation if intrarenal Ang II levels is mediated in part by AT 1 -receptor-mediated uptake of Ang II.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C Tmentioning
confidence: 99%
“…9 This transgenic rat line (strain name: TGR[Cyp1a1-Ren2]) was created by inserting the mouse Ren2 renin gene, fused to an 11.5 kb fragment of the cytochrome P450 1a1 (Cyp1a1) promoter, into the genome of the Fischer 344 rat. 9 Cyp1a1, which catalyses the oxidation of a wide range of endogenous lipophilic compounds and xenobiotics, [10][11][12] is not constitutively expressed, but is highly inducible upon exposure to various aryl hydrocarbons such as indole-3-carbinol (I3C). [10][11][12][13][14][15][16] Induction of Cyp1a1 is mediated by the aryl hydrocarbon receptor, which is a basic helix-loophelix-transcription factor that binds to specific DNA elements in the Cyp1a1 promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many examples of drugs and xenobiotics (Forrester et al 1992), including caffeine (Gandhi & Khanduja, 1992) and ethanol (Lucas et al 1992), which increase some P450 involved in phase I metabolism. Other non-nutrient components of human foods which have been shown to have this effect include the flavonoids tangeretin, flavone and nobiletin .…”
Section: A)mentioning
confidence: 99%
“…The metabolism of halofantrine by CYP3A therefore implies that, the interindividual variation in the activity of this enzyme in both the liver and gut wall [42,43], and also variation caused by enzyme induction or enzyme inhibition [44,45], may contribute to the known variable disposition of the drug. In contrast, it is unlikely that CYP2D6 genotype will be a major determinant of halofantrine disposition.…”
Section: Discussionmentioning
confidence: 99%